2009
DOI: 10.1590/s1516-14392009000400021
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of polypyrrole films on aluminum surfaces from a p-toluene sulfonic acid medium

Abstract: Electrodeposition of polypyrrole films on aluminum from aqueous solutions containing p-toluene sulfonic acid and pyrrole was performed by cyclic voltammetry and galvanostatic technique. The influence of applied current density on the morphology of the films was studied by Scanning Electron Microscopy. The films displayed a cauliflower-like structure consisting of micro-spherical grains. This structure is related to dopand intercalation in the polymeric chain. Films deposited at higher current density were more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 28 publications
4
13
0
5
Order By: Relevance
“…Fig. 4 shows typical 'cauliflower' like structures on the electrolyte-facing surface of such films, similar to those previously observed at polypyrrole films polymerised in the presence of p-toluene sulfonic acid [41]. Notably, the film surface is not flat, but consists of a series of peaks and valleys with considerable surface roughness associated with a high degree of film porosity.…”
Section: Scanning Electron Microscopic Study Of Polypyrrole-acid Red supporting
confidence: 75%
“…Fig. 4 shows typical 'cauliflower' like structures on the electrolyte-facing surface of such films, similar to those previously observed at polypyrrole films polymerised in the presence of p-toluene sulfonic acid [41]. Notably, the film surface is not flat, but consists of a series of peaks and valleys with considerable surface roughness associated with a high degree of film porosity.…”
Section: Scanning Electron Microscopic Study Of Polypyrrole-acid Red supporting
confidence: 75%
“…3b) electrodes illustrating the surface morphology of the free standing films. The morphology of the both films features a cauliflower-like nodule structure composed of microspherical grains, which is related to dopant intercalation in the polymeric chain [18]. The free-standing films can be rolled up (inset of Fig.…”
mentioning
confidence: 99%
“…(Eslami et al, 2019) Regarding the state of the art of the theme addressed in this study, it is observed that references on "Chemical and electrochemical deposition of polypyrrol on lead alloy surface" are scarce (Eftekhari & Ahmadi, 2006). Regarding deposition on metallic substrates such as magnesium, copper, aluminum, zinc, stainless steel, there is a good database previously published (Menkuer & Ozkazank, 2019;Vera et al, 2014;Sheng et al, 2014;Mortazavi et al, 2019;Samad et al, 2019;Sharifirad et al, 2010;Annibaldi, Rooney, & Breslin, 2012;Ferreira, Liu, & Cho, 2018;Souza, Liu, & Cho, 2018;Liu, Bezerra, & Cho, 2017).…”
Section: Introductionmentioning
confidence: 91%